THE ASSOCIATION OF PHYSIOLOGICAL STRESS AND RELATED QUALITY OF LIFE AMONG STROKE AND HYPERTENSION PATIENTS IN DISTRICT LAYYAH, PUNJAB, PAKISTAN. (The Research of Medical Science Review, 2024)
Hypertension is the main cause of cerebral small vessel disease, which results in cognitive impairment and stroke. Long-term stroke risk (that appears months or years after starting or stopping the medicine) is 4-5 times higher than the short-term risk (temporary medical coverage). It is the most significant risk factor for various neurological issues. Additionally, the risk of stroke is significant in the presence of hypertension, A systematic review design, with a sample size of 136 participants. The study duration was set at 6 months, conducted in District Layyah, PUNJAB, PAKISTAN. Data was collected using questionnaires. Descriptive analysis was performed using SPSS version 22, In order to designate the study inhabitants in terms of sex, age, stress level, and quality of life,frequency tables were created. Using Spear man correlation coefficient, each dimension of eminence of life was connected with the constant adaptable physiological stress. In this study T test and correlation of each questionnaire was applied to check the significance p value, Compared to individuals with high blood pressure, QOL is more liable to be impacted by the disability caused by the stroke itself and less by physiological depress and socio-demographic variables in individuals with hypertension and stroke. The specificfeatures of people with mild to moderate stroke may be significant to consider when devising comprehensive, focused therapies meant to maximize recovery and enhance HRQOL.